Ernst Fuchs (1851-1930) und die Weltgeltung der Wiener Ophthalmologischen Schule um 1900: Eine biografische Dokumentation mit Ergänzungen und Erläuterungen - SCHMIDT-WYKLICKY, Gabriela (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
By presenting documents and original photographs of the ophthalmologist Ernst Fuchs his life and scientific work are presented in a way never done before.